Health gains, costs and cost-effectiveness of a population-based screening programme for abdominal aortic aneurysms. Issue 8 (22nd May 2019) - Nair, N; Kvizhinadze, G; Jones, G T; Rush, R; Khashram, M; Roake, J; Blakely, A
Abstract: Background: Abdominal aortic aneurysm (AAA) rupture carries a high fatality rate. AAAs can be detected before rupture by abdominal ultrasound imaging, allowing elective repair. Population-based screening for AAA in older men reduces AAA-related mortality by about 40 per cent. The UK began an AAA screening programme offering one-off scans to men aged 65 years in 2009. Sweden has a similar programme. Currently, there is no AAA screening programme in New Zealand. This cost–utility analysis aimed to assess the cost-effectiveness of a UK-style screening programme in the New Zealand setting. Methods: The analysis compared a formal AAA screening programme (one-off abdominal ultrasound imaging for about 20 000 men aged 65 years in 2011) with no systematic screening. A Markov macrosimulation model was adapted to estimate the health gains (in quality-adjusted life-years, QALYs), health system costs and cost-effectiveness in New Zealand. A health system perspective and lifetime horizon was adopted. Results: With New Zealand-specific inputs, the adapted model produced an estimate of about NZ 15 300 (€7746) per QALY gained, with a 95 per cent uncertainty interval (UI) of NZ 8700 to 31 000 (€4405 to 15 694) per QALY gained. Health gains were estimated at 117 (95 per cent UI 53 to 212) QALYs. Health system costs were NZ 1·68 million (€850 535), with a 95 per cent UI of NZ 820 200 to 3·24 million (€415 243 to €1·65 million). Conclusion: Using New Zealand's gross domestic product per capita (about NZ 45 000 or €22 100) as a cost-effectiveness threshold, a UK-style AAA screening programme would be cost-effective in New Zealand. Graphical Abstract: Currently, there is no abdominal aortic aneurysm (AAA) screening programme in New Zealand. This cost–utility analysis aimed to assess the cost-effectiveness of a UK-style screening programme in the New Zealand setting. With New Zealand-specific inputs, the adapted model produced an estimate of about NZ 15 300 per QALY gained (€7746), with a 95 per cent uncertainty interval of NZ 8700 to 31 000 (€4405 to 15 694). Using New Zealand's gross domestic product per capita (about NZ 45 000 or £22 100) as a cost-effectiveness threshold, a UK-style AAA screening programme would be cost-effective in New Zealand. Cost-effective in New Zealand too